MOTIVASI MAHASISWA PENYIAR PADA PROGRAM ACARA LINTAS KAMPUS DI PRO 2 RRI SURAKARTA - Hardika Putri, Veronica Oktaviana (Transformasi, 2015)
This research is descriptionqualitativethat aim at to know motivation college students to bepresenter on lintaskampus show at Pro 2 RRI Surakarta. The research ussed analysisinteractive, the research results show that the college students motivation to be a presenter inthe lintaskampus show program can be divided into 2 type that are intrinsic and extrinsic.Key Words: Radio Broadcast, Profession Announcer,, Motivation